2006
DOI: 10.1002/ana.20807
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of endocytic and autophagic pathways in a lysosomal storage disease

Abstract: The vastly increased autophagic buildup may be responsible for skeletal muscle damage and prevent efficient trafficking of replacement enzyme to lysosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
199
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 275 publications
(218 citation statements)
references
References 46 publications
15
199
2
1
Order By: Relevance
“…Notably, there appeared to be fewer, although much larger lysosomes in comt mutants ( Figure 5, J-L, arrowheads). This enlargement of lysosomes is similar to that observed in cathepsin-D mutants (Khurana et al 2010), as well as in a variety of lysosomal storage diseases (Fukuda et al 2006). The enlarged lysosomes could result from a lack of lysosomal turnover.…”
Section: Comt Mutants Cannot Sustain Autophagysupporting
confidence: 84%
“…Notably, there appeared to be fewer, although much larger lysosomes in comt mutants ( Figure 5, J-L, arrowheads). This enlargement of lysosomes is similar to that observed in cathepsin-D mutants (Khurana et al 2010), as well as in a variety of lysosomal storage diseases (Fukuda et al 2006). The enlarged lysosomes could result from a lack of lysosomal turnover.…”
Section: Comt Mutants Cannot Sustain Autophagysupporting
confidence: 84%
“…Furthermore, we have shown that autophagic accumulation in muscle fibers was associated with resistance to enzyme replacement therapy. [21][22][23] We now demonstrate that the underlying skeletal muscle pathology and the extent of autophagy in Pompe patients are similar to those in mice. Autophagy appears to play a major role in the pathogenesis of the disease, a finding that has important implications for the effectiveness of enzyme replacement therapy with the recombinant human acid a-glucosidase.…”
Section: Introductionmentioning
confidence: 51%
“…Eventually, in old mice, the autophagic mass replaced most of the muscle tissue. 20,21 Although the presence of autophagic vacuoles with cytoplasmic degradation products in muscle biopsies from patients with Pompe disease was noted many years ago, 16 the phenomenon has received little attention until recently. 28 We have now established that the abnormal autophagy in skeletal muscle is a major feature in the pathology of the disease in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The defective autophagy in Pompe disease, which is blatantly evident in muscle fibers and to a certain extent in a cell model, may stem from reduced availability of energy source due to lysosomal glycogen sequestration. 44,45 A disturbed energy metabolism has recently been documented in Pompe patients with the adult form of the disease. 46 The autophagic defect contributes to the pathogenesis of muscle damage and alters trafficking of the replacement enzyme to the lysosome in Pompe disease.…”
Section: Discussionmentioning
confidence: 99%